2018
DOI: 10.17221/8/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

An unusual foreign body in a cat: a case report

Abstract: Foreign bodies that affect airways are a well-recognised problem in small-animal practice. Cats in par ticular, may be especially at risk of aspiration due to their predatory behaviour. Here, we report a case of an insect as a foreign body, namely a beetle in the tracheal bifurcation of a cat. Radiographs suggested a wide range of possibilities for differential diagnosis, but the presence of a foreign body was initially suspected. A final diagnosis was not pursued by the owner and the cat was euthanised. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Leal et al (2015) reported that radiographic examinations were 92% successful in making an accurate diagnosis of foreign bodies in the respiratory system. In this case, as in studies of other researchers (Agudelo et al 2018;Cagatay et al 2018;Lewitt et al 1993;Somrup et al 2017), the foreign body Han et al / FAVE Cs. Vet.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Leal et al (2015) reported that radiographic examinations were 92% successful in making an accurate diagnosis of foreign bodies in the respiratory system. In this case, as in studies of other researchers (Agudelo et al 2018;Cagatay et al 2018;Lewitt et al 1993;Somrup et al 2017), the foreign body Han et al / FAVE Cs. Vet.…”
Section: Discussionsupporting
confidence: 65%
“…Obstruction cases caused by foreign bodies in the respiratory tract of dogs are rarely encountered in veterinary literature (Cagatay et al 2018;Leal et al 2015;Somrup et al 2017). Foreign bodies in the respiratory tract cause clinical findings, especially dyspnea and cough (Agudelo et al 2018;Leal et al 2015;Lewitt et al 1993;Somrup et al 2017). In this study, the clinical diagnosis and treatment method of a dog with complaints of dyspnea and severe cough was discussed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations